The Development of Android-Based Educational Games on Work and Energy Material to Train Critical Thinking Skills - Syuwari, Hanifah Ridho; Mawardi, Ari Cahya (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2025)
Critical thinking has emerged as an essential skill for students to master in the 21st century. The topic on work and energy is difficult for students, this is due to limitation in learning media in terms of helping students, especially those based on technology. This study aimed to investigate: 1) The features of Android-based educational games designed to enhance critical thinking skills among eighth-grade students of SMP/MTS, 2) The quality of the Android-based educational games in achieving the critical thinking skills train on work and energy topic among eighth-grade students of SMP/MTS, 3) Students' perceptions of Android-based educational game on the topic of work and energy to train the critical thinking skills among eighth-grade students of SMP/MTS, 4) Enhancement of critical thinking skills among eighth-grade SMP/MTS students. This research applied a 4D model of Research and Development (R&D) that was restricted to the development stage. The research employed instruments for experts, teachers, and students. The data analysis involved V Aiken's validation, mean calculations, and N-Gain. The results of this study included: 1) the creation of learning media in the form of an educational game named GEDUSI (Energy and Work Education Games), 2) The quality of the education game developed by researchers is included in the Very Good category, 3) Student responses agree as a practical and fun learning media, 4) This game can improve students' critical thinking skills.